2018
DOI: 10.13057/biodiv/d190107
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: The existence of Javan Leopard (Panthera pardus melas Cuvier, 1809) in the non-conservation forest areas of Cisokan, Cianjur, West Java, Indonesia

Abstract: Shanidah SS, Partasasmita P, Hudoso T. Parikesit, Febriato P, Meganatara EN. 2018. Short Communication: The existence of Javan Leopard (Panthera pardus melas Cuvier, 1809) in the non-conservation forest areas of Cisokan, Cianjur, West Java, Indonesia. Biodiversitas 19: 42-46. There is no accurate data about the number of individual leopards in Java Island in both conservation and nonconservation areas. In West Java, deforestation for plantations and agriculture is widespread, although it is unknown if leopard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 2 publications
0
9
0
2
Order By: Relevance
“…Rural people of Cisokan watershed knew three kinds of tigers in the area, namely macan loreng or lodaya (Panthera tigris sondaica), macan tutul or macan totol (Panthera pardus melas), and macan kumbang (Panthera pardus) is a black panther of sub-species of panther. Panthera tigris sondaica was considered to be extinct in West Java region before 1980s (Whitten et al 1999;Iskandar 2014), but Panthera pardus was still found in the Cisokan upper watershed (Shanida et al 2018) Like most rural Sundanese people, rural people of Bojong Salam and Sukaresmi Villages have myths on tigers. They believe that the King of Pajajaran (Western Java), Prabu Siliwangi, transformed into a tiger after he died.…”
Section: Myth Of Leopardmentioning
confidence: 99%
“…Rural people of Cisokan watershed knew three kinds of tigers in the area, namely macan loreng or lodaya (Panthera tigris sondaica), macan tutul or macan totol (Panthera pardus melas), and macan kumbang (Panthera pardus) is a black panther of sub-species of panther. Panthera tigris sondaica was considered to be extinct in West Java region before 1980s (Whitten et al 1999;Iskandar 2014), but Panthera pardus was still found in the Cisokan upper watershed (Shanida et al 2018) Like most rural Sundanese people, rural people of Bojong Salam and Sukaresmi Villages have myths on tigers. They believe that the King of Pajajaran (Western Java), Prabu Siliwangi, transformed into a tiger after he died.…”
Section: Myth Of Leopardmentioning
confidence: 99%
“…Leopards are particularly fond of areas that have trees for shelter and lurking activities as they are strong climbers (Gunawan et al 2012). Besides being found in natural forests, leopards in Cisokan are also found in production forests -pine forests where there are many human activities and planting coffee plants (Shanida et al 2018). According to Gunawan et al (2012), the Javan leopard does not only use pine forests exclusively as its main habitat, but it also uses other types of vegetation for its daily activities, even it uses caves, rocky outcrops, and grooves or dried rivers as its shelter.…”
Section: Mammalian Diversitymentioning
confidence: 99%
“…In addition, interviews with residents of the Babakan Bandung village and other villages indicated some problems of leopards' feeding on people's dogs and goats (LIPI 2012). According to Shanida et al (2018a), leopard was found in Pasir Nangka, Pasir Laja, Sarongge, Batu Nagok, Pasir Taman, Batununggul, Cilengkong, Cisuren, Cigintung, Cileungsing, Cipanas, and Pasir Bedil/Japarana. The other protected species, Leopard cat was found in Datarmala, Pasir Bedil, Cirumamis, Cilengkong, Batununggul, Pasir Taman, Cigintung, Ciawitali, and Sarongge (Shanida et al 2018b).…”
Section: Mammalsmentioning
confidence: 99%